The SLC25A42 Transcript Is a Biomarker for Fetal Reprogramming in Response to Placental Insufficiency in Preterm Newborns Under 32 Weeks Gestation—A Pilot Study - Chou, Fu-Sheng; Wang, Pei-Shan (Frontiers in Pediatrics, 2020)
Introduction: Timing of medical delivery of preterm newborns exposed to placental insufficiency is largely determined by umbilical artery blood flow and maternal clinical manifestations. There is a lack of tools to properly assess fetal body response to placental insufficiency before or upon delivery. Yet, short- and long-term comorbidities associated with placental insufficiency and the consequential intrauterine growth restriction may be a result of fetal response following prolonged stress. This study aims to establish a procedure to investigate fetal/neonatal transcriptional response to placental insufficiency as part of an initiative to identify cost-effective biomarkers for assessing fetal response to placental insufficiency. Methods: A prospective pilot study involving newborns with birth gestation < 32 weeks was conducted to compare gene expression profiles in whole blood collected at birth among three clinically distinct groups - preeclampsia without placental insufficiency (PE), placental insufficiency (PI), and non-PE/PI groups. Results: Whole blood from 11, 3, and 6 newborns in the non-PE/PI, PE, and PI groups were obtained. A transcriptome analysis found that the majority of the genes were downregulated in the PI group, suggesting global transcriptional inactivation. Intriguingly, SLC25A42, which encodes a mitochondrial transporter for coenzyme A and adenosine-3’,5’-diphosphate, was significantly upregulated in the PI group. Conclusion: Transcriptional biomarkers for assessing fetal response to placental insufficiency may provide a useful tool to better understand the pathophysiology of fetal reprogramming in response to placental insufficiency. The validity and the role of SLC25A42, as well as its correlation with short- and long-term neonatal outcomes, warrants further investigation.